Model Pengembangan Nilai Agama Islam pada Siswa Slow Learner untuk Penguatan Moderasi Beragama - Almaydza Pratama Abnisa; Zubairi Zubairi; Lutfia Nursanti (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This research aims to develop an effective learning model for instilling Islamic religious values, particularly those related to religious moderation, in slow-learning students in inclusive schools. Slow-learning students require an adaptive and structured instructional approach to understand abstract concepts such as religious moderation.The model developed integrates a visual-kinesthetic approach, experiential learning, and the use of interactive digital media, adapted to their learning characteristics. The trial results showed a significant increase in students' understanding and moderate attitudes toward diversity. This model is recommended as a practical guide for Islamic Religious Education (PAI) teachers in supporting inclusive education and strengthening national character.